The impact of supply constraints on bank lending in the euro area - crisis induced crunching? - Hannah Sabine Hempell; Christoffer Kok (European Central Bank (ECB), 2010)
Aggregate loan development typically hinges on a combination of factors that impact simultaneously on the demand and the supply side of bank lending. The financial turmoil starting in mid-2007 had detrimental consequences for banks' balance-sheets, cost of funds and profitability, thus weighing negatively on their ability to supply new loans. This paper examines the impact of supply constraints on bank lending in the euro area with a special focus on this turmoil period. The empirical evidence presented suggests that banks' ability and willingness to supply loans affects overall bank lending activity in general and has done so particularly during the financial crisis. Applying a cross-country panel-econometric approach using a unique confidential data set on results from the Eurosystem's bank lending survey allows us to disentangle loan supply and demand effects. We find that even when controlling for the effects coming from the demand side loan growth is negatively affected by supply-side constraints. This applies both for loans to households for house purchase and for loans to non-financial corporations. We furthermore provide evidence that the impact of supply-side constraints, especially related to disruptions of banks' access to wholesale funding and their liquidity positions, was reinforced since the eruption of the financial crisis and corresponding adjustments in banks' loan portfolios seem to have been geared primarily via prices rather than outright quantity restrictions.
Keywords: C23; E51; E52; G21; 330; bank credit; euro area; loan supply constraints; panel data; Kredit; Kreditrationierung; Eurozone; EU-Staaten